PEG-fusion of viable sciatic nerve isografts restores axonal structure and behavioral recovery after segmental-loss sciatic nerve injuries in Lewis rats - Cathy Z. Yang; Liwen Zhou; Alexander M. Schafer; Alexa N. Olivarez; Guhan Periyasamy; Varun Gokhale; Rhea Sood; Henry A. Garcia; Arjun Agarwal; Joseph F. Alderete; George D. Bittner (PLoS ONE, 2026)
Segmental-loss peripheral nerve injuries (SL-PNIs) often produce severe deficits in sensory/motor functions and voluntary behaviors. The current gold standard for repair is neurorrhaphy of a cable autograft that (1) produces donor site morbidity; (2) results in rapid Wallerian degeneration (WD) of severed distal nerve segments; (3) relies on slow (1–2 mm/day) axonal regeneration; (4) does not prevent atrophy of denervated muscles and sensory structures; and (5) results in poor to non-existent recovery of sensory/motor functions and voluntary behaviors, especially with longer segmental-loss gaps and/or with denervated targets located rather distal to a proximal SL-PNI. Our study used genetically identical Lewis rats as a model system for isograft transplants. Neurorrhaphy of viable peripheral nerve isografts (VPNIs) of 5- or 10-mm length was performed to repair sciatic SL-PNIs of 4- or 8-mm gap length, respectively. Animals were repaired with a set of well-specified solutions that did (PEG-fusion group) or did not (Negative Control [NC] group) contain 50% w/w 3.35 kDa polyethylene glycol (PEG), an axolemmal fusogen at that specific weight and concentration. We also examined the effects of locally applied FK506 on 10-mm VPNI repairs both with and without PEG-fusion. We hypothesized that PEG-fusion groups would show better axonal morphology and behavioral recovery, as assessed by the Sciatic Functional Index (SFI), compared to NC groups regardless of the gap length. We also hypothesized that FK506 would improve the effects of PEG-fusion by reducing inflammation. Our data showed that PEG-fused VPNI groups had significantly larger axonal diameters and lower g-ratios, less WD, and better SFI scores compared to NC groups regardless of the gap lengths for SL-PNIs. However, localized FK506 treatment only transiently improved axonal regeneration and impaired long-term SFI behavioral recovery, which is the most important measure of successful repairs. In conclusion, PEG-fusion repair technologies show great potential for improving clinical treatments.